Peran Pancasila dalam Menangani Konflik Hukum Perkawinan antara Hukum Islam dan Hukum Nasional: The Role of Pancasila in Handling Marriage Legal Conflicts Between Islamic Law and National Law - Ahmad Muhamad Musain Nasoha; Ashfiya Nur Atqiya; Siti Kholifaturrahmah; Ardika Rahmawati; Azizah Adzra Fauziyyah (LITERA: Jurnal Ilmiah Mutidisiplin, 2024)
This research aims to analyze the role of Pancasila in resolving marriage legal conflicts between Islamic law and national law in Indonesia.The legal context of marriage in Indonesia is often characterized by tension between Islamic law which regulates based on sharia principles and national law regulated in Law Number 1 of 1974 concerning Marriage.Pancasila, as the foundation of the Indonesian state, plays an important role in harmonizing and resolving these conflicts. This research examines how the principles of Pancasila, namely Belief in One God, Just and Civilized Humanity, Indonesian Unity, Democracy Led by Wisdom in Deliberation/Representation, and Social Justice for All Indonesian People can be integrated to resolve marriage legal problems.Through a literature review of books, the latest journals, and expert opinions, this research found that Pancasila can function as an ethical and normative basis for formulating harmonious legal policies.This research recommends the application of Pancasila principles in the legislative process and resolution of marriage legal conflicts to achieve justice and harmony between the various legal systems in force in Indonesia.